Perbedaan Penyeduhan Kopi Dengan Metode Siphon, French Fresh, Dan Moka Pot - Bincar Parningotan Simbolon (JURAGAN - Jurnal Agroteknologi, 2024)
This research aims to analyze differences in the organoleptic characteristics of coffee brewed using three methods, namely siphon, French press, and moka-pot. The practicum was carried out by brewing two types of coffee, namely Temanggung Palm Sugar robusta coffee (Coffee A) and Jambi coffee (Coffee B), using these three methods. Organoleptic test results show that there are significant variations in taste, aroma, color, clarity and aftertaste based on the brewing method. The siphon method tends to produce coffee with better clarity, while the moka-pot produces coffee with a deeper color. The conclusion shows that the brewing method influences the final characteristics of the coffee.